Computational Observation of an Ion Permeation Through a Channel Protein. Issue 1 (February 1998) - Suenaga, Atushi; Komeiji, Yuto; Uebayasi, Masami; Meguro, Toshiyuki; Saito, Minoru; Yamato, Ichiro
Abstract : The ion permeation process, driven by a membrane potential through an outer membrane protein, OmpF porin of Escherichia coli, was simulated by molecular dynamics. A Na + ion, initially placed in the solvent region at the outer side of the porin channel, moved along the electric field passing through the porin channel in a 1.3 nsec simulation; the permeation rate was consistent with the experimentally estimated channel activity (10 8 ∼10 9 /sec). In this simulation, it was indicated that the ion permeation through the porin channel proceeds by a "push-out" mechanism, and that Asp113 is an important residue for the channel activity.